Referential Dependencies in Turkish: Some Novel Arguments on the Binding of Kendisi, O and Pro - Nazik DİNÇTOPAL DENİZ (Dilbilim Araştırmaları Dergisi)
The Turkish reflexive kendisi (self-3SG.POSS) deviates from Principle A of the Binding Theory and from the Minimalist movement approaches to referential dependencies. This paper concurs with Kornfilt (2001) and provides further support that kendi-si is preceded by a null possessor (pro) which influences its binding but argues that kendisi is not a reflexive. Kendisi’s distribution changes when its possessor is a null pronominal (pro) or an overt pronominal (o, ‘she/he/it’). It is claimed that pro and o are not the null and overt counterparts of the same pronominal. Pro and o show the same distribution only in (in)direct object positions. In possessive phrases and subject positions, their distributions differ. Following Cardinaletti and Starke (1999) and Safir (2004), it is argued that pro is a weak pronoun which only refers to an antecedent mentioned in the context. But o is a strong pronoun and can make independent reference and function as a topic shifter.